2021
DOI: 10.1159/000519261
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Renal Replacement Therapy Delivery in Swedish Intensive Care Units during the COVID-19 Pandemic

Abstract: <b><i>Background:</i></b> The COVID-19 pandemic led to a rapidly increased demand for intensive care unit (ICU) and renal replacement therapy (RRT) worldwide. RRT delivery was threatened by a lack of specially trained staff and equipment. We investigated how the first wave of COVID-19 affected RRT delivery in Swedish ICUs. <b><i>Methods:</i></b> An Internet-based questionnaire was sent to ICU lead physicians which included quantitative and qualitative questions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Thus, it has been crucial to take measures to combat the spread of SARS-CoV-2 in dialysis facilities where physical distancing is difficult to practice (45). On the other hand, early reports in areas with high COVID-19 incidence indicated that a nontrivial number of patients without ESKD had AKI and required inpatient dialysis at hospital due to COVID-19 (46, 47). It is possible that this depletion of hospital resources in some cases might have led to early discharges for some patients with ESKD who were on dialysis before they were sufficiently clinically stable, and the strain on health care providers might have impeded typical postdischarge care coordination processes between the hospital and dialysis facility.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been crucial to take measures to combat the spread of SARS-CoV-2 in dialysis facilities where physical distancing is difficult to practice (45). On the other hand, early reports in areas with high COVID-19 incidence indicated that a nontrivial number of patients without ESKD had AKI and required inpatient dialysis at hospital due to COVID-19 (46, 47). It is possible that this depletion of hospital resources in some cases might have led to early discharges for some patients with ESKD who were on dialysis before they were sufficiently clinically stable, and the strain on health care providers might have impeded typical postdischarge care coordination processes between the hospital and dialysis facility.…”
Section: Discussionmentioning
confidence: 99%
“…During the height of COVID-19 pandemic, the developed world was confronted with a sudden surge in the number of patients with severe AKI putting tremendous strain on the healthcare system [16]. Many countries faced acute shortages of ICU beds, CRRT machines, and trained ICU staff, exposing the shortcomings of the prevailing healthcare infrastructures and exclusive reliance on CRRT for managing AKI [12].…”
Section: Introductionmentioning
confidence: 99%
“…AKI is a well-described complication of COVID-19 critical illness, including high rates of renal replacement therapy (RRT) and (especially during the initial surge) lower-than-expected rates of renal recovery (8)(9)(10)(11)(12)(13). Given the frequency of resource constraints-and risks of rationed care-in earlier pandemic waves, a detailed understanding of critically ill patients at risk for AKI and RRT might have informed planning and allocation of finite resources such as RRT devices and supplies, appropriately trained staff, and electrolyte replacement fluids (14)(15)(16)(17), which necessitated alterations in dialysis dosing, schedule, modality, and staffing in prior waves (18,19). In this applied example, we provide insight into the practicalities and pitfalls of using multistate modeling in critical care outcomes research.…”
mentioning
confidence: 99%